Pyelonephritis xanthogranulomatosa - case report (2 cases) - M. Szymanek-Szwed; K. Załęska-Oracka; J. Samotyjek; K. Jobs; B. Jurkiewicz (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2019)
Pyelonephritis xantogranulomatosa is a very rare form of chronic kidney inflammation. Only a few hundred cases have been described in children. The cause of the disease is not fully understood, but it is strongly correlated with urolithiasis. The inflammatory process usually involves one kidney and is diffuse, rarely a form limited to the part of the parenchyma is seen. The most common symptoms are abdominal pain, fever, weight loss, lack of appetite. In imaging tests the kidney is enlarged, with a preserved shape, contains deposits in the calyx and pelvic system and numerous hypoechogenic changes indicating abscesses. The most frequently isolated pathogens are E. coli and P. Mirabillis. The authors present 2 cases treated in our center due to Pyelonephritis xantogranulomatosa. In both cases a nephrectomy was performed.